Perbedaan Pemberian Jus Tomat Dan Jus Wortel Terhadap Tekanan Darah Lansia Penderita Hipertensi Kecamatan Bawen - Blessa Adhy Nugraha; Suwanti Suwanti; Umi Aniroh (Program Studi S1 Keperawatan Universitas Ngudi Waluyo, 2019)
Hypertension is the most common disease in the elderly and causes death worldwide every year. Hypertension disease can be controlled non pharmacologically such us using tomato juice and carrot juice. To know the different effect of carrot juice and tomato juice to blood pressure of elderly hypertension patients in Lemahireng Village, Bawen Sub-district, Semarang Regency. This type of research was Quasy Experiment using Two - Group Pre Post Test Design. The samples in this study were 30 people with 15 samples of carrot juice group and 15 samples of tomato juice. Blood pressure was measured using a sphygmomanometer. Data analysis used dependent t-test and independen tt-test (α = 0,05). In the carrot juice group, the average systole before administering carrot juice was 165.73mmHg and after it was 149.87 mmHg, while diastole before administering carrot juice was 95.33 and after it was 88.73 mmHg. In the tomato juice group, the average systole before administering tomato juice was 164.47 and after it was 150.53 mmHg, whereas diastole before administering tomato juice was 93.00 and 85.53 mmHg afterwards. There is no significant difference in the effect of administering carrot juice and tomato juice to lower blood pressure. Carrot juice or tomato juice can be used as a non-pharmacological treatment for hypertensive patients.Key words: Hypertension, Carrot juice, Tomato juice